1974
DOI: 10.1021/ja00822a038
|View full text |Cite
|
Sign up to set email alerts
|

Rates and products of addition of 4-chlorobenzenesulfenyl chloride to the tert-butylethylenes

Abstract: + rnh2ingly, the kobSd at pH 14 are expected to be rather insensitive to substituent effects, while the other a priori conceivable mechanism, addition of water to the ion of the Schiff base, would cause a strong influence of substituents on k(l4). As a matter of fact, the observed values of k( 14) are about the same for all the substituted salicylidenes. If, however, reaction 4 is isolated, the calculated values of k4 depend strongly on the a's as may be seen in Figure 5 (p = 2.85).All the kinetically importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
2

Year Published

1974
1974
1990
1990

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
9
2
Order By: Relevance
“…The available evidence is not in accord with this possibility. Addition occurs in an anti stereospecific rilanner in all cases, even for cisand trans-l,2-di-tert-butylethylene (17). For all unsyrninetrical alkenes products with anti-Markownikoff as well as Markownikoff orientation are obtained.…”
Section: +1mentioning
confidence: 85%
See 1 more Smart Citation
“…The available evidence is not in accord with this possibility. Addition occurs in an anti stereospecific rilanner in all cases, even for cisand trans-l,2-di-tert-butylethylene (17). For all unsyrninetrical alkenes products with anti-Markownikoff as well as Markownikoff orientation are obtained.…”
Section: +1mentioning
confidence: 85%
“…In the extrenle case with two [err-butyl groups, it is possible that the electrophile will be forced out of its usual path, perpendicular to the plane of the alkene, and attack at a more obliquc angle. Such an explanation has been proposed t o explain the large difference in rates of addition of bromine and arenesulfenyl chloride to cis-and tratis-1,'-cli-terr-butylethylenes (16,17).…”
Section: +1mentioning
confidence: 99%
“…The latter reaction is generally accepted to involve a strongly bridged intermediate, and occurs in an anti fashion to each of these compounds (35). Oxymercuration however, leads to the same product from each of these isomeric alkenes (17b).…”
mentioning
confidence: 99%
“…Borane 11 reacted smoothly in solution with molecular oxygen, affording directly the trans fused decalone 12. High-temperature hydroboration of 2 proceeded normally to afford an 88:12 mixture of diols 9 and 10. These experimental results are largely explicable in terms of severe steric hindrance of the double bond in 2, and a direct comparison with the reactivity of the closely related acyclic olefin 1 is made.…”
mentioning
confidence: 98%
“…Steric effects on the properties and reactivities of appropriately substituted olefins have been the subject of a number of recent investigations.1 Syntheses of sterically hindered olefins are generally difficult to achieve, and it is only recently that a synthesis of the highly hindered olefin tri-tert-butylethylene (1) has been effected by Abruscato and Tidwell.2 These authors have also reported on the effect of such steric hindrance on the Raman,2 ultraviolet,3 and 13C NMR spectra,4 and on the chemical reactivity of the double bond in l.5 The influence of steric effects on the reactivity of the double bond in 1 stems both from hindrance to attack by the tert-butyl groups and from torsional strain at the double bond induced by relief of steric compression.6 Separation of these two effects is not possible in such acyclic systems such as 1 but they can be largely separated if the double bond is incorporated into an appropriately substituted ring system.…”
mentioning
confidence: 99%